2020
DOI: 10.3390/v12070728
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 6 Knockout Mice Exhibit Higher Susceptibility to Influenza A Virus Infection

Abstract: The host innate defence against influenza virus infection is an intricate system with a plethora of antiviral factors involved. We have identified host histone deacetylase 6 (HDAC6) as an anti-influenza virus factor in cultured cells. Consistent with this, we report herein that HDAC6 knockout (KO) mice are more susceptible to influenza virus A/PR/8/1934 (H1N1) infection than their wild type (WT) counterparts. The KO mice lost weight faster than the WT mice and, unlike WT mice, could not recover their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…To gain insight into the pro-viral mechanism of NAA60, we investigated its role in IAV-induced host innate antiviral response, because, previously, we identified that the HDACs exerts their anti-IAV function via this pathway ( 9 11 , 13 ). Furthermore, the IAV-induced expression of IFNα was downregulated in HDAC11-depleted cells ( 13 ) and HDAC6-knockout mice ( 14 ). To determine if the opposite was true in NAA60-depleted cells, A549 cells were transfected with the control or NAA60 siRNA and infected with PR8 at an MOI 1.0.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain insight into the pro-viral mechanism of NAA60, we investigated its role in IAV-induced host innate antiviral response, because, previously, we identified that the HDACs exerts their anti-IAV function via this pathway ( 9 11 , 13 ). Furthermore, the IAV-induced expression of IFNα was downregulated in HDAC11-depleted cells ( 13 ) and HDAC6-knockout mice ( 14 ). To determine if the opposite was true in NAA60-depleted cells, A549 cells were transfected with the control or NAA60 siRNA and infected with PR8 at an MOI 1.0.…”
Section: Resultsmentioning
confidence: 99%
“…The acetyltransferases, Gcn5 and PCAF are involved in the suppression of the expression of host type I IFN and ISGs such as STAT1, MX1 and viperin ( 15 ), p300/CBP are implicated in the regulation, both positive and negative, of the expression of multiple host proteins involved in various stages of IAV life cycle ( 29 ), whereas NAA20/25 and also Gcn5 and PCAF facilitate the positive regulation of the IAV polymerase and host shutoff activities through acetylation of viral proteins ( 16 , 31 , 32 ). In contrast, HDAC6 ( 14 ) and HDAC11 ( 13 ) are involved in the enhancement of the IAV-induced type I IFN production. In addition, HDAC 1, 2, 4, and 11 also are implicated in the enhancement of the STAT1 phosphorylation as well as the expression of ISGs like viperin, IFITM3 and ISG15 during IAV infection ( 9 11 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that the pro-viral role of HDAC6 ZnF domain during IAV uncoating influenced the infection outcome. In contrast, another recent study in which another strain of HDAC6 knockout mice was infected with IAV showed them to be more susceptible to PR8 H1N1 infection than their wild type counterpart [ 225 ]. In this work, it was argued that the absence of HDAC6 leads to a blunted innate response and concomitantly increased susceptibility of mice to IAV infection.…”
Section: In Focus: Influenza Virus Capsid Uncoatingmentioning
confidence: 99%
“…Pharmacological inhibition of HDAC6 increased trafficking of viral components to the plasma membrane and viral release, a mechanism probably involving acetylated microtubules [ 313 ]. More recently, Hdac6 −/− mice were shown to be slightly more susceptible to influenza infection, which was actually correlated with a downregulation of several innate immune pathways [ 314 ]. Further clarification on the impact and the role of HDAC6 is therefore required.…”
Section: Iav Restriction Factorsmentioning
confidence: 99%